PENINGKATAN PRESTASI BELAJAR MATEMATIKA MELALUI PERAGA ULAR TANGGA PADA SISWA KELAS 1 SDN GONDANGLOR II KECAMATAN SUGIO KABUPATEN LAMONGAN - Sunarti Sunarti (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2022)
The main problem to be answered in this study is: Can the snake and ladder demonstration in Mathematics learning improve the learning achievement of grade 1 students at SDN Gondanglor II, Sugio District, Lamongan Regency. Each cycle is a series of activities consisting of 1) Planning, to identify problems and plan learning activities, and create research instruments; 2) Acting, carrying out learning in the Mathematics subject matter of addition, subtraction of two-digit numbers; 3) Observing, collecting data through test results and observation sheets, 4) Reflecting, analyzing observed data. The subjects in this study were all 10 grade 1 students at SDN Gondanglor II, Sugio District, Lamongan Regency, totaling 10 students. This classroom action research uses snakes and ladders visualizers during Mathematics learning. From the results of research that has been done shows that using snakes and ladders visualizer can improve student achievement.